Metformin-Induced Generalized Bullous Fixed-Drug Eruption with a Positive Dechallenge-Rechallenge Test: A Case Report and Literature Review - Bahareh Abtahi-Naeini; Tooba Momen; Rezvan Amiri; Parvin Rajabi; Fereshte Rastegarnasab (Case Reports in Dermatological Medicine)
Metformin is a commonly used medication in diabetic patients. It can cause different complications including cutaneous adverse reactions. Metformin-induced fixed-drug eruption (FDE) has been reported in limited cases. Due to the popularity of metformin, clinicians need to be aware of uncommon drug reactions for proper diagnosis and treatment. Herein, we report a 43-year-old man with generalized bullous lesions with a positive dechallenge-rechallenge test diagnosed as metformin-induced generalized bullous fixed-drug eruption. Metformin dosage was stopped and lesions were treated with topical clobetasol propionate and oral prednisolone and cyclosporine-A. After a 6-month follow-up, he was well without any relapsing episodes.